Comparison of Wells Score, D–Dimer and Combination of Wells Score and D–Dimer with Venous Duplex Ultrasonography in Diagnosis of Acute Deep Vein Thrombosis in Lower Extremity - Lesmana, Andy; Pratama, Dedy; Wangge, Grace (The New Ropanasuri Journal of Surgery, 2017)
Introduction. Diagnosis of acute deep vein thrombosis (DVT) of lower extremity using available diagnostic tools such as venous duplex ultrasonography (VDUS) encountered problems including cost, time consuming and the operator. A simple and practical tool is required. Thus, we run a study aimed to evaluate the efficacy of Wells score, D–Dimer, or combination of both, compared to VDUS in early detection of acute DVT of lower extremity. Method. A diagnostic study was run using cross–sectional design in Department of Surgery enrolling all adult subjects of which suspected to acute DVT of lower extremity managed in period of January 2014 –December 2015 who met the criteria. The diagnosis was confirmed by VDUS. Those data of medical record were analyzed statistically with diagnostic study to find out the sensitivity and specificity. Results. The study enrolled of 85 subjects. The prevalence of acute DVT of lower extremity was 65.88%. Sensitivity and the highest negative predictive value of 100.00% were found in score combination of II and IV. While as the highest specificity of 89.66% and the highest positive predictive value of 92.68% were found in score combination of III. The score with balanced diagnostic value (sensitivity of 87.50% and specificity of 72.41%) was found in Wells score 3 level I. Conclusion. Wells score and VDUS showed comparable efficacy in detection of acute DVT of lower extremity. Thus, a score could be used as a diagnostic tool.